SUSPENSI DAN ENDAPAN SEDIMEN DI PERAIRAN LAUT JAWA - Helfinalis, Helfinalis (UI Scholars Hub, 2023)
Suspension and Sedimentation Studies in Java Sea Water. Oceanography study of the Java Sea Water has been done on September 2004. The lowest total suspended solid in the water surface was 0.018 gr/l at the south part of Kalimantan and the highest was 0.053 gr/l at the west part of South Kalimantan. The lowest total suspended solid values in the medium sea level was about 0.023 gr/l at the west part of Pancel and reaches the value of 0.051 gr/l at the west part of South Kalimantan. At the bottom of deep sea level, the lowest total suspended solid value were about 0.022 gr/l at the west by south of South Kalimantan and the highest was found in the west part of South Kalimantan which has the value of 0.051 gr/l. The sediment has a yellowish brown color in the depth of several centimeters which indicates of highly sedimentation supply from the river. Sediment at the bottom of South Kalimantan waters which is located near the land was found more like a mud on the surface and silt on the inside